Eklezjalne dogmaty wiary katolickiej w świadomości dorosłych katolików polskich z przełomie wieków - Baniak, Józef (Humaniora. Czasopismo Internetowe, 2021)
In this paper, the author discusses a number of issues referred to in the title, namely: 1) the religious dimension of the Church as a community founded by Jesus Christ; 2) the spiritual dimension of the Church as a community of believers – the Church as the Mystical Body of Christ; 3) the essential characteristics of the Church: one, holy, universal, apostolic; 4) the religious-salvific as well as the social role of the institutional Church. The analyses in this paper rely on the findings from sociological studies and social surveys conducted in the latter half of the 20th century and in the subsequent two decades of the 21st century among adult Polish Catholics concerning their attitude towards the ecclesial dogmas of the Catholic faith. An examination of those results demonstrate a direction of changes in how adult Catholics perceive and assess the features and the religious mission of the Church in both periods in question, i.e. at the turn of the century. In the current century, the proportion of adult Catholics who accept the ecclesial dogmas of the faith have been somewhat lower than it was the case in the second half of the 20th century. Similarly, the ratios of Catholics who acknowledged the religious-salvific and social role of the Church in the religiosity and life of the lay adherents were higher in the past century.